The impact of energy crisis on variance- and Gini-optimized portfolio structures – case of Hungary - Tömöri, Gergő; Csontos, György (Economica, 2025)
Crises in the 2020s have shocked global stock markets with unprecedented sud- denness. This has had a particularly strong impact on the Central European countries outside the euro area and exposed to heightened geopolitical conflicts, and within them, Hungary, which has had a particular government response to the crisis. Our research objective was to investigate the impact of the energy crisis on the Hungarian stock market as a consequence of the combination of greening policies, the post-Covid reopening and the EU sanctions policy on Russian energy imports, focusing on the portfolio optimization of the Hungarian blue chips and the stocks of the biggest complex (renewable and non-renewable) energy producer and trader company in the Hungarian market. In this context, our aim is to determine the impact of the turbulent crisis phenomena in the period 2020-2023, with a focus on energy price inflation, on the structure of a portfolio of the 5 stocks mentioned above optimized based on mean-variance and mean-Gini model. Since based on both methods, although differently, significantly increased the portfolio weight of the same energy company stocks in the energy crisis, it can be concluded that the change in the composition of the diversified portfolio reflected the impact of macroeconomic conditions on the stock market.